(3GdJLGQI GdNGQLjIs ((3GdLRGFQ(B:s (3OGQ CLjGd GdQbej (B,s, 2023)
(3jJWQb gPG GdcJGH Edi GdJCUjd GdfXQj ddJLGQI GdNGQLjI ef NdGd SHYI aUhd aj eGjdj (B: (3CSGSjGJ Mhd GdJLGQI GdNGQLjI(B:(3eGgjI GdJLGQI GdOhdjI(B-(3GdJLGQI GdNGQLjI hGdJLGQI GdOGNdjI(B-(3CSHGH bjGe GdJLGQI GdNGQLjI, fXQjGJ GdJLGQI GdNGQLjI(B:(3fXQjGJ GdJLGQI bHd GdcdGSjc(B-(3GdfXQjI GdcdGSjcjI(B-(3GdfXQjI GdfjhcdGSjcjI hGdMOjKI ddJLGQI GdNGQLjI, GdSjGSGJ GdJLGQjI(B: (3eaghe hCgOGa SjGSGJ GdJLGQI GdNGQLjI(B-(3CfhGY SjGSGJ GdJLGQI GdNGQLjI(B-(3COhGJ GdSjGSGJ GdJLGQjI, JMQjQ GdJLGQI GdNGQLjI(B:(3eGgjI GdJMQjQ GdJLGQj(B-(3CTcGd GdJMQjQ GdJLGQj heDTQGJ bjGSg(B-(3JMdjd GdJLGQI aj Xd GdefXeI GdYGdejI ddJLGQI, ejRGf GdeOahYGJ GdOhdj(B: (3eGgjI ejRGf GdeOahYGJ(B-(3echfGJ ejRGf GdeOahYGJ(B-(3GdJhGRf hGdGNJdGd aj ejRGf GdeOahYGJ, SYQ GdUQa(B: (3eGgjI SYQ GdUQa(B-(3CfXeI SYQ GdUQa(B-(3fXQjGJ JMOjO CSYGQ GdUQa, GdJLGQI GdGdcJQhfjI(B: (3eGgjI GdJLGQI GdGdcJQhfjI(B-(3eejRGJ hJMOjGJ GdJLGQI GdGdcJQhfjIs
Keywords: (3GdJLGQI GdNGQLjIs; (3GdJLGQI GdOhdjIs